Sport specialization and fitness and functional task performance among youth competitive gymnasts - Root, H.; Marshall, A. N.; Thatcher, A.; Snyder Valier, A. R.; Valovic McLeod, T. C.; Bay, R. C. (Journal of Athletic Training, 2019)
Context Gymnastics trains fundamental movement skills but has high rates of early sport specialization. Early specialization is associated with increased injury risk. Gymnasts devote time to developing technical skill, but whether specialization status influences performance is unknown.